Study on Apoptosis of Squamous Cell Carcinoma Using Photothermal Therapy with Partial Injection of Gold Nanoparticles - Kim, Donghyuk; Kim, Hyunjung (Nanoscale and Microscale Thermophysical Engineering, 2023)
Recently, the incidence of skin cancer has been increasing owing to the development of science and technology and the increase in outdoor activities. Research on photothermal therapy as a treatment technique for similar skin cancer is in progress. Photothermal therapy is a treatment technique that removes tumor tissue by increasing the temperature. It has the advantage of rapid recovery and a low risk of secondary infection. In this study, a numerical investigation of photothermal therapy based on heat transfer is conducted on squamous cell carcinoma present inside the skin layer. Analysis is performed by varying the number of injections of gold nanoparticles, volume fraction of gold nanoparticles in the tumor, and laser intensity. In addition, conditions for maximizing expression of apoptosis in the tumor and minimizing amount of thermal damage to surrounding normal tissues are identified through the variable which is apoptosis retention ratio, thermal hazard value and effective apoptosis retention ratio. It was confirmed that the optimal therapeutic effect was shown when the volume fraction of injected GNPs was 10−3, the number of injections was 6 times, and the irradiated laser intensity was 140 mW for the tumor presented in this study. Ultimately, these results are expected to accelerate the commercialization of photothermal therapy.
Keywords: Gold nanoparticle; Gold Nanoparticles; Laser intensities; MonteCarlo methods; Partial injection; Photothermal therapy; Skin cancers; Squamous cell carcinoma; Thermal damage; Treatment techniques; Gold nanoparticles; Monte Carlo method; partial injection; photothermal therapy; thermal damage